Analysis of black soil environment based on Arduino. (May 2017) - Li, Y; Zhang, Y F; Wu, C H; Wang, J F
Abstract: As everyone knows, the black soil of Heilongjiang bred rice is famous in the world. How to use networking technology to detection the growth environment of Heilongjiang rice, and expands it to the local planting environment to our country is the most important topic. However, the growth environment of rice is complex. In current research, some importnat factors such as carbon dioxide, oxygen, temperature and humidity, pH value and microbial content in black soil that affect the growth of plants are selected, and a kind of black land based on data acquisition and transmission system based on the Arduino development environment and the mechanism construction of Kingview has been realized. The collected data was employed to establish the simulation environment for the growth of rice in Heilongjiang. It can be applied to stimulate the rice growing environment of Heilongjiang province, and gives a improvement of rice quality in other areas. Keywords: Arduino; Kingview; living environment